Percutaneous coronary revascularization in coronary artery disease: Lessons from a single center experience1. Issue 1 (8th November 2012) - Aksoy, Olcay; Tuzcu, E. Murat; Ellis, Stephen G.; Whitlow, Patrick L.; Cam, Akin; Batizy, Lillian; Agarwal, Shikhar; Franco, Irving; Bajzer, Christopher; Simpfendorfer, Conrad; Raymond, Russell; Nair, Ravi; et al.
Abstract Objectives To determine the role of percutaneous coronary intervention (PCI) and its impact on mortality in coronary artery disease (CAD). Background It's unclear whether PCI provides benefit in patients with CAD outside of acute settings. We sought to determine the role of PCI and its effect on mortality in patients with similar entry criteria to prior RCTs and compare outcomes with medical treatment. Methods Using institutional diagnostic catheterization database of consecutive patients undergoing coronary angiography from 1/2004 to 1/2010, we examined records for patients with a positive stress test and >70% coronary stenosis or symptoms of angina and >80% coronary stenosis. We excluded those with acute coronary syndromes, low ejection fraction (EF), history of CABG, and CABG following index catheterization. We stratified patients by treatment and performed unadjusted and propensity matched analyses. The outcome was all‐cause mortality obtained from the social security death index. Results We identified 3, 375 patients using study inclusion criteria. Mean age was 65 ± 11 years and 69% (n = 2, 332) were men. Mean EF was 55% ± 8%. In the unadjusted cohort, 1, 265 patients received medical management and 2, 110 received PCI. The unadjusted analysis revealed significantly better survival in PCI patients (P < 0.0001) (HR: 0.51; 95% confidence interval (CI), 0.41–0.63). Propensity matching was performed for 1, 580 patients and analysis showed better survival among patients receiving PCI (0 = 0.04) (HR: 0.74; 95% CI, 0.55–0.98). PCI continued to show better survival after excluding patients with malignancy (P = 0.03) and unstable angina (P = 0.007). Conclusions This single center registry analysis demonstrated better survival in stable CAD patients undergoing PCI compared to medical management alone. These data suggest there may be a benefit of PCI beyond symptom relief. Future randomized trials are needed to further understand the role of PCI in broader patient populations. © 2012 Wiley Periodicals, Inc.